Eu não fiquei parado : um olhar sobre as práticas pedagógicas desenvolvidas durante a pandemia da Covid-19 direcionadas aos alunos surdos - Matos, Cristiane Ribeiro Batista (2023)
The present study proposes to investigate pedagogical practices that were developed during the Covid-19 pandemic with regard to science and mathematics education in Libras, observing the use (or not) of technological instruments in a state school. It is perceived that the deaf need to be included in the technological era in order to, in this way, feel an active part in the educational process, and, for this, it is necessary to observe that, at the present time, several resources are available, which demand knowledge for its application. But are they available for use by schools? In order to carry out a thought-provoking debate about the intersections on the subject, it relies on the subsidies of some theorists and scholars, such as: Libâneo (1994), Barbosa e Souza (2010), Vygotsky (2008, 2010, 2011, 2012 and 2016), Sales, Penteado and Moura (2015), Fava (2018), Führ (2018), Passos (2022), among others, who highlighted the theme. In order to reach the objectives, a bibliographical, descriptive and qualitative research was applied, for which it was supported by legislation, specific books, scientific articles and thesis/dissertations to analyze whether, truly, there are encounters between the pedagogical practices, the technological instruments available and teaching science and mathematics to the deaf. It also used a collection of information about the feelings of teachers through interviews. As a result, it is perceived that one cannot idealize an evolved society without thinking of ways to really include everyone in society, unfolding this knowledge to include the disabled person, in this approach, the deaf person. Knowledge has been presented as a true and effective tool to proceed, in this sense, competence and skill are needed, since science is the foundation and from it the inclusion process has greater possibilities of being carried out consistently.